Assessment of some trace elements in African catfish (Clarias gariepinus) from Hadejia-Nguru Wetlands, Northern Nigeria - Musa, Musa Alhaji; Sani, Dahiru; Saba, Abdulwakil Olawale; Azmai, Mohammad Noor Amal; Nazarudin, Muhammad Farhan; Ahmad Amshi, Maimuna (Springer Science and Business Media, 2025)
This study investigates seasonal and spatial variations in trace element concentrations (Cu, Nb, Pt, Fe, Hg) in Clarias gariepinus from Nigeria’s Hadejia-Nguru Wetlands, a RAMSAR site critical to regional food security. Muscle and kidney tissues were analyzed using SEM–EDX to assess contamination levels against WHO/FAO maximum residue limits (MRLs). Results revealed seasonal dynamics: Cu in muscle peaked during the dry season (0.10 ppm and BDL in wet season), while Fe in kidneys was higher in the wet season (2.58 ppm vs. 1.86 ppm). Spatially, Nb and Pt concentrations were highest in Nguru (kidney: 0.45 ppm Nb, 0.15 ppm Pt), while Fe dominated in Margadu (2.98 ppm). Mercury was detected only in Margadu kidneys (0.07 ppm). Health risk indices (EDI, THQ, HI) indicated elevated risks for Fe in Margadu, particularly among fishers (HRI = 297.14), though most elements remained below WHO/FAO limits. The inclusion of Nb and Pt, rarely monitored in African aquatic systems, highlights emerging contamination concerns. These findings underscore the need for targeted pollution control and dietary advisories to mitigate health risks in vulnerable populations reliant on wetland resources.